Isolation of New Chalcone from the Leaves of Bauhinia variegata - Maheswara, M.; Koteswara Rao, Y.; Siddaiah, V.; Venkata Rao, C. (Asian Journal of Chemistry, 2010)
A new chalcone, 2´-hydroxy-4´,6´-dimethoxy-3,4-methylenedioxy chalcone (1) together with two known flavonol glycosides, kaempferol-3-O-D-glucopyranoside (2) and kaempferol-3-O left - α-L-rhamnoside (3) were isolated from the leaves Bauhinia variegata. The structure of 1 was elucidated by ESIMS, UV, ID and 2D NMR spectroscopy including COSY, HSQC and HMBC experiments. These compounds were found to display interesting antifungal activity against Aspergillus niger and Candida albacans.